How to Generate Profitable Growth in Engineering Small and Medium Enterprises. A Case Study Analysis - Mathey, Mauricio (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4817 Small and medium enterprises (SMEs) play a fundamental role in the Peruvian economy because they significantly contribute to job creation. However, many of these companies face challenges to generate profitable growth and, therefore, improve the quality of life of their workers and stakeholders. This article examines the actions that a medium-sized engineering company can take in order to generate profitable growth. The research used a quantitative and qualitative case study methodology to achieve a comprehensive understanding of the company and its competitive environment. As a result of the research, four actions are proposed, which would lead to a company’s growth if they are jointly implemented.